2015
DOI: 10.1002/alr.21567
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Onodi cell and new classification of sphenoid sinus for endoscopic sinus surgery

Abstract: Classification of the anterior wall of the sphenoid sinus based on the Onodi cell allows 3-dimensional assessment of the shape of the sphenoid sinus. We believe that the sphenoid sinus can be opened safely by full preoperative assessment of the anterior wall type, the position of the superior turbinate, and the position of the ostium of the sphenoid sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 23 publications
1
26
1
2
Order By: Relevance
“…[ 5 ], Nomura et al [ 11 ], and Chmielik et al [ 20 ]. The results of this study revealed higher prevalence of SEC than the CT studies of Al-Abri et al [ 21 ], Leunig et al [ 22 ] and Pérez-Pińas et al [ 23 ], and our results were also lower than the CT reports of Kasemsiri et al [ 24 ], Wada et al [ 25 ] and Tomovic et al [ 4 ]. In addition, in a CT study involving the patients with both rhinosinusitis and healthy volunteers, the SEC prevalence was found to be 9% in healthy volunteers and 7% in the patients with rhinosinusitis [ 26 ].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…[ 5 ], Nomura et al [ 11 ], and Chmielik et al [ 20 ]. The results of this study revealed higher prevalence of SEC than the CT studies of Al-Abri et al [ 21 ], Leunig et al [ 22 ] and Pérez-Pińas et al [ 23 ], and our results were also lower than the CT reports of Kasemsiri et al [ 24 ], Wada et al [ 25 ] and Tomovic et al [ 4 ]. In addition, in a CT study involving the patients with both rhinosinusitis and healthy volunteers, the SEC prevalence was found to be 9% in healthy volunteers and 7% in the patients with rhinosinusitis [ 26 ].…”
Section: Discussioncontrasting
confidence: 74%
“…In the light of the above data, regarding the inclusion criteria, studies on SEC prevalence have been performed either on chronic sinus disease as this study or on randomly paranasal sinus CTs or cadaveric specimens. The prevalence of SEC in our study was performed on chronic sinus disease and our results were compared with the CT studies of Nomura et al [ 11 ] and Wada et al [ 25 ]. This study's results were also higher than healthy individuals in the CT study (Table 5 ).…”
Section: Discussionmentioning
confidence: 91%
“…A histopathological investigation revealed polyps in the Onodi cell. Wada et al 13 examined the efficacy of the identification of the Onodi cell and the classification of the sphenoid sinus using sagittal CT for a sphenoidotomy. These authors studied CT images of the patients' sinuses (n ¼ 261; 522 sides).…”
Section: Discussionmentioning
confidence: 99%
“…15 This disease typically occurs during childhood with progressive bilateral visual loss because of the neurodegeneration of retinal ganglion cells; multifactorial events may influence both its onset and phenotype. [13][14][15] Pretegiani et al 15 reported a neuro-ophthalmologic assessment of an Italian group of patients focusing on 60 OPA1 mutations carriers (52 symptomatic) belonging to 13 families. The authors discovered four known mutations, the most common being a lack of conscience c1034G > A, and a new missense mutation, c1193A > C. This new missense mutation was found in a 54-year-old woman with the late-onset phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…It is not practical to use the anterior wall of the sphenoid sinus because of its variation; that is, the anterior wall of the sphenoid sinus can exist either anterior to, inside, or posterior to the optic canal. 12 On sagittal images in which the optic nerve crossed the lamina papyracea, we defined the first wall anterior to the optic canal as the first wall (FW). We classified the PEA position relative to the FW as follows ( Figure 1 ): type 1, the PEA is located posterior to the FW; type 2, the PEA is located inside the FW; type 3, the PEA is located in the ethmoid cells facing the FW posteriorly; type 4, the PEA is located inside the second wall anterior to the optic canal; and type 5, the PEA is located anterior to the second wall that is anterior to the optic canal.…”
Section: Methodsmentioning
confidence: 99%